Ventricular Tachycardia Ablation in Severe Heart Failure: An International Ventricular Tachycardia Ablation Center Collaboration Analysis. (January 2017) - Tzou, Wendy S.; Tung, Roderick; Frankel, David S.; Vaseghi, Marmar; Bunch, T. Jared; Di Biase, Luigi; Tholakanahalli, Venkatakrishna N.; Lakkireddy, Dhanunjaya; Dickfeld, Timm; Saliaris, Anastasios; Weiss, J. Peter; Mathuria, Nilesh; et al.
Abstract : Background—: Ventricular tachycardia (VT) radiofrequency ablation has been associated with reduced VT recurrence and mortality, although it is typically not considered among New York Heart Association class IV (NYHA IV) heart failure patients. We compared characteristics and VT radiofrequency ablation outcomes of those with and without NYHA IV in the International VT Ablation Center Collaboration. Methods and Results—: NYHA II–IV patients undergoing VT radiofrequency ablation at 12 international centers were included. Clinical variables, VT recurrence, and mortality were analyzed by NYHA IV status using Kaplan–Meier analysis and Cox proportional hazard models. There were significant differences between NYHA IV (n=111) and NYHA II and III (n=1254) patients: NYHA IV had lower left ventricular ejection fraction; more had diabetes mellitus, kidney disease, cardiac resynchronization implantable cardioverter–defibrillator, and VT storm despite greater antiarrhythmic drug use ( P <0.01). NYHA IV subjects required more hemodynamic support, were inducible for more and slower VTs, and were less likely to undergo final programmed stimulation. There was no significant difference in acute complications. In-hospital deaths, recurrent VT, and 1-year mortality were higher in the NYHA IV group, in the context of greater baseline comorbidities. Importantly, NYHA IV patients without recurrent VT had similar survival compared with NYHA II and III patients with recurrent VT (68% versus 73%). Early VT recurrence (⩽30 days) was significantly associated with mortality, especially in NYHA IV patients. Conclusions—: Despite greater baseline comorbidities, VT radiofrequency ablation can be safely performed among NYHA IV patients. Early VT recurrence is significantly associated with subsequent mortality regardless of NYHA status. Elimination of recurrent VT in NYHA IV patients may reduce mortality to a level comparable to NYHA II and III with arrhythmia recurrence. Abstract : Supplemental Digital Content is available in the text.